UJI AKTIVITAS ANTIFUNGAL KULIT MANGGIS (Garcinia mangostana) DAN SEMANGKA (Citrullus vulgaris)TERHADAP Trichophyton mentagrophytes PENYEBAB DERMATOMYCOSIS - Tengku Putri Sholihah; Atria Martina; Yuharmen ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Dermatomycosis is the most common infection diseasesuffered by inhabitants of tropical countries and caused by  Trichophyton mentagrophytes. Mangosteen and watermelon epicarp have high phytochemical compounds which is potential as antibacterial, antifungal and antioxidant. This study aimed to determine antifungal activity of mangosteen and watermelon epicarp against  Trichophyton mentagrophytes. The study was conducted using completely randomizedfactorial design. Epicarp of mangosteen and watermelon were processed to fresh and dry extracts with concentration 40% and 80% (fresh extract) and 5%, 10% and 20% (dry extract). Dry extract were dissolved using 3 different solvent, e.g: aquabides, heated aquabides and etyl alcohol. Antifungal activity was tested using paper disc method. The results showed that almost all of watermelon and mangosteen epicarp dry extract had antifungal activity againts  Trichophyton mentagrophytes,  while fresh extract did not showed antifungal activity againts  Trichophyton mentagrophytes.  The highest antifungal activity of watermelon was showed in 20% extract in heated aquabides with inhibition zone diameter is 36,8 mm. The highest antifungal activity of mangosteen was showed in 10% extract in heated aquabides with inhibition zone diameter is 28,5 mm.